The Phenomenon of Religious Tourism at the Sanctuary of Senhor Bom Jesus de Matosinhos in Congonhas (MG) - Fernandes, Nayara Souza; Pires, Maria do Carmo (Anais Brasileiros de Estudos Turísticos, 2022)
The Sanctuary of Senhor Bom Jesus de Matosinhos in Congonhas (MG) hosts an architectural and sculptural complex of undeniable artistic and cultural value, however, the site differs from other religious heritage sites in that while these sites usually attract a large public due to their historical and artistic value, the Sanctuary has a significant amount of religious tourism which makes it one of the largest pilgrimage sites in the country. Within this perspective, the study attempts to understand the factors that justify this phenomenon, performing an analysis of the Sanctuary, that takes into account its material and symbolic universe, as well as data on tourist visitation at the location. The research points out that the large influx of religious tourism is a result of the secular celebration of the Jubilee of the Bom Jesus de Matosinhos that takes place in the vicinity of the Sanctuary, however, it is concluded that the real element responsible for this phenomenon lies in the junction between the material and the intangible, in the field of practices and cultural exchanges that are provided by the festival, which in turn is conditioned to the materiality of the Sanctuary.